PENGARUH LATIHAN SENAM AEROBIC LOW IMPACT TERHADAP KUALITAS TIDUR PADA LANSIA PENDERITA HIPERTENSI DI DESA SUSUHBANGO KABUPATEN KEDIRI - Azhar Nur Hidayatullah, Muhammad; Rosidah, Nikmatur; Sondang Irawan, Dimas (Jurnal Kesehatan Tambusai, 2024)
Elderly people are elderly people aged 60-70 years. Elderly people often experience health problems such as hypertension which can cause sleep disorders. Sleep disturbances that last a long time will result in a decrease in sleep quality which will have an impact on the quality of life. Low impact aerobic exercise is a non-pharmacological therapy option to help overcome sleep quality problems in the elderly. Low impact aerobic exercise has easy and simple movements so it doesn't burden the elderly. This study aims to determine the effect of low impact aerobic exercise on sleep quality in elderly people with hypertension in Susuhbango Village, Kediri Regency. The method used was pre-experimental with a one group pretest-posttest design, the population and sample of this study were elderly people with hypertension who had sleep quality problems in Susuhbango Village, Kediri Regency. This research was carried out by providing intervention in the form of low impact aerobic exercise to the elderly for 1 month 3 times a week. Data were collected using the PSQI questionnaire to determine the level of sleep quality of elderly people during pretest-posttest. The data was processed using the Wilcoxon signed test to determine the effect of low impact aerobic exercise training on sleep quality in elderly people with hypertension in Susuhbango village, Kediri district. Based on the test results using the Wilcoxon signed test, a significant result of p = 0.001 was obtained, where p < 0.05, which means that H? is rejected and H? is accepted, so there is a significant effect of providing low impact aerobic exercise on sleep quality in elderly people with hypertension in Susuhbango Village. Kediri Regency. It can be concluded that there is an influence of low impact aerobic exercise training on sleep quality in elderly people with hypertension in Susuhbango Village, Kediri Regency